Peter Jarvis and the understanding of adult learning. Issue 1 (4th March 2017) - Illeris, Knud
Abstract: By comparing Peter Jarvis' understanding of learning with two other approaches – which Jarvis himself has referred to as 'the most comprehensive': Etienne Wenger's 'social theory of learning' and my own psychologically oriented theory of 'the three dimensions of learning' – it becomes evident that Jarvis' understanding is distinguished by its strong foundation in philosophical considerations combined with detailed studies of adults' learning in relation to practical assignments. It also appears that there are no fundamental discrepancies between the three approaches so that it is possible to use them complementary and thereby get a very broadly covering basis for dealing with learning and education in practice.